Examining patterns of dose response for clients who do and do not complete cognitive processing therapy. (December 2019) - Holmes, Samantha C.; Johnson, Clara M.; Suvak, Michael K.; Sijercic, Iris; Monson, Candice M.; Wiltsey Stirman, Shannon
Highlights: In a community-based RCT, 58% of clients completed all 12 sessions of CPT. Most treatment noncompletion occurred between sessions two and five. Clients who improved at a greater rate attended more sessions. The average client needed to attend at least 10 sessions for favorable outcomes. Abstract: Trauma-focused therapies, including Cognitive Processing Therapy (CPT; Resick et al., 2016), are effective at reducing clients' PTSD symptoms. A limitation to these treatments, however, is client completion of them. The current study examined temporal patterns of treatment non-completion and the relationships among non-completion, PTSD, and overall mental health functioning outcomes, among clients in a randomized controlled CPT implementation trial. Two models of symptom change were tested: 1) dose-effect model (i.e., clients uniformly improve with additional sessions at a negatively accelerating rate); and 2) the good-enough level model (i.e., clients remain in therapy until they have achieved sufficient improvement, thus clients who attend fewer sessions improve at quicker rates). Results indicated that 42% of clients did not complete treatment, with most discontinuing between sessions two and five. Data did not fit the dose-effect or good-enough level model. Rather, clients who improved at a greater rate in their PTSD symptoms and overall mental health functioning attended more sessions. The average client had the best outcomes when they completed all 12 sessions. Identifying clients who may be at risk for discontinuing treatment, and making a concerted effort toward retaining them, is imperative to reduce non-completion rates and ultimately improve client outcomes.